Networking Badan Amil Zakat Nasional Jawa Barat dalam Meningkatkan Pelayanan Zakat - Irfan Sanusi (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2016)
Network of Zakat acts as a bridge between the National Amil Zakat Agency (Baznas) with other stakeholders who have interests with Baznas. This research will reveal about the scope of networking, the principle of networking, and the goal of networking achievement by Baznas in West Java Province in the service of zakat. Using qualitative descriptive method, the research finds the principles of building networking Baznas West Java, namely: the principle of participation, the principle of mutual cooperation, the principle of trust, the principle of right enforcement, and Obligation, leads to Right-Obligation, Reward And Punishment, and the principle of sustainability. Through the application of this networking principle Baznas West Java Province has partners who can be invited to work together mutually benefit.